Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's plot five points on the parabola given by the equation [tex]\( y = (x+3)^2 + 1 \)[/tex]. We'll choose five values for [tex]\( x \)[/tex], calculate the corresponding [tex]\( y \)[/tex] values, and then plot those points.
1. Choosing the first value for [tex]\( x \)[/tex]:
- Let [tex]\( x = -5 \)[/tex]
- Substitute [tex]\( x = -5 \)[/tex] into the equation:
[tex]\[ y = (-5 + 3)^2 + 1 = (-2)^2 + 1 = 4 + 1 = 5 \][/tex]
- The first point is [tex]\( (-5, 5) \)[/tex].
2. Choosing the second value for [tex]\( x \)[/tex]:
- Let [tex]\( x = -3 \)[/tex]
- Substitute [tex]\( x = -3 \)[/tex] into the equation:
[tex]\[ y = (-3 + 3)^2 + 1 = 0^2 + 1 = 0 + 1 = 1 \][/tex]
- The second point is [tex]\( (-3, 1) \)[/tex].
3. Choosing the third value for [tex]\( x \)[/tex]:
- Let [tex]\( x = -1 \)[/tex]
- Substitute [tex]\( x = -1 \)[/tex] into the equation:
[tex]\[ y = (-1 + 3)^2 + 1 = 2^2 + 1 = 4 + 1 = 5 \][/tex]
- The third point is [tex]\( (-1, 5) \)[/tex].
4. Choosing the fourth value for [tex]\( x \)[/tex]:
- Let [tex]\( x = 0 \)[/tex]
- Substitute [tex]\( x = 0 \)[/tex] into the equation:
[tex]\[ y = (0 + 3)^2 + 1 = 3^2 + 1 = 9 + 1 = 10 \][/tex]
- The fourth point is [tex]\( (0, 10) \)[/tex].
5. Choosing the fifth value for [tex]\( x \)[/tex]:
- Let [tex]\( x = 2 \)[/tex]
- Substitute [tex]\( x = 2 \)[/tex] into the equation:
[tex]\[ y = (2 + 3)^2 + 1 = 5^2 + 1 = 25 + 1 = 26 \][/tex]
- The fifth point is [tex]\( (2, 26) \)[/tex].
So, the five points on the parabola [tex]\( y = (x+3)^2 + 1 \)[/tex] are:
[tex]\[ (-5, 5), (-3, 1), (-1, 5), (0, 10), (2, 26) \][/tex]
These points can be plotted on a graph to visualize the parabola.
1. Choosing the first value for [tex]\( x \)[/tex]:
- Let [tex]\( x = -5 \)[/tex]
- Substitute [tex]\( x = -5 \)[/tex] into the equation:
[tex]\[ y = (-5 + 3)^2 + 1 = (-2)^2 + 1 = 4 + 1 = 5 \][/tex]
- The first point is [tex]\( (-5, 5) \)[/tex].
2. Choosing the second value for [tex]\( x \)[/tex]:
- Let [tex]\( x = -3 \)[/tex]
- Substitute [tex]\( x = -3 \)[/tex] into the equation:
[tex]\[ y = (-3 + 3)^2 + 1 = 0^2 + 1 = 0 + 1 = 1 \][/tex]
- The second point is [tex]\( (-3, 1) \)[/tex].
3. Choosing the third value for [tex]\( x \)[/tex]:
- Let [tex]\( x = -1 \)[/tex]
- Substitute [tex]\( x = -1 \)[/tex] into the equation:
[tex]\[ y = (-1 + 3)^2 + 1 = 2^2 + 1 = 4 + 1 = 5 \][/tex]
- The third point is [tex]\( (-1, 5) \)[/tex].
4. Choosing the fourth value for [tex]\( x \)[/tex]:
- Let [tex]\( x = 0 \)[/tex]
- Substitute [tex]\( x = 0 \)[/tex] into the equation:
[tex]\[ y = (0 + 3)^2 + 1 = 3^2 + 1 = 9 + 1 = 10 \][/tex]
- The fourth point is [tex]\( (0, 10) \)[/tex].
5. Choosing the fifth value for [tex]\( x \)[/tex]:
- Let [tex]\( x = 2 \)[/tex]
- Substitute [tex]\( x = 2 \)[/tex] into the equation:
[tex]\[ y = (2 + 3)^2 + 1 = 5^2 + 1 = 25 + 1 = 26 \][/tex]
- The fifth point is [tex]\( (2, 26) \)[/tex].
So, the five points on the parabola [tex]\( y = (x+3)^2 + 1 \)[/tex] are:
[tex]\[ (-5, 5), (-3, 1), (-1, 5), (0, 10), (2, 26) \][/tex]
These points can be plotted on a graph to visualize the parabola.
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.